Syzygium polyanthum protects against hypertensive induced kidney damage in spontaneous hypertensive rat model - Liza Noordin; Nurul Syahida Ramli; Nor Hidayah Abu Bakar; Wan Amir Nizam Wan Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2021)
Syzygium polyanthum is traditionally used as anti-hypertensive agent. However, the nephroprotective effects of S. polyanthum against hypertensive induced chronic kidney disease has yet to be elucidated. This study was conducted to determine the antioxidant properties and nephroprotective effects of aqueous extract of S. polyanthum (AESP) in the spontaneous hypertensive rat model (SHR). The phytochemical constituent was identified using the phytochemical screening and HPLC methods. The in vitro antioxidant activities were determined by DPPH radical scavenging and ferric reducing antioxidant power (FRAP) assays. Fifty male SHR were equally divided into 5 groups, (n=10/group); Untreated-SHR, 20 mg/kg Losartan-treated SHR, 1500 mg/kg AESP treated SHR, 1750 mg/kg AESP treated SHR and 2250 mg/kg AESP treated SHR, while 10 male Wistar Kyoto rats (WKY) were used as control. Losartan and AESP were administered by oral gavage. Rats were sacrificed after 12 weeks of experiment. The phytochemicals include phenolics, flavonoids and alkaloids were identified. AESP has high antioxidant activity as shown by antioxidant assays. AESP normalised systolic blood pressure (p<0.05) and significantly improved renal function (p<0.05). AESP also significantly reduced malondialdehyde (MDA) (p<0.05) and increased superoxide dismutase (SOD) levels in the serum as compared to untreated-SHR group (p<0.05). Ultrastructure of renal damage improved by supplementation of AESP. Conclusively, S. polyanthum is potential to alleviate hypertensive induced chronic kidney disease through its antioxidant properties.